Profile, lifestyle, and level of work stress of call center agents in selected call centers in Iloilo City. - Saluta, Rio Estrada
This study sought to determine the profile of the call center agents in selected call centers in Iloilo city, thier lifestyle, and their level of work stress, Forty-four call center agents from three registered call centers in Iloilo City served as the respondents of the study., The Profile Indicator, Lifestyle Indicator, and Work Stress Profile were utilized for data gathering. Results showed that majority of the agents are single and belong to the 21-23 age bracket. Their estimated monthly income ranges from php 5,000-15,000. They allocate their income for food, rent, clothing, transportation, mobile phone fees and entertainment. Agents experience low level of work stress on the interpersonal relationships and physical condition dimension. This implies that support personnel in call centers in Iloilo City are competent and efficient and the agents interact with their colleagues with ease and confidence. The conditions in the office are also stressful to the agents since they are equipped with proper training before they started their work. On the job interest dimension, agents experience high level of work stress, due to factors like boredom, routine work and job insecurity.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Call centers -- Iloilo City